Competitive Advantages from Horizontal Relationships in Productive Agglomerations: perceptions of local agents - Deboçã, Leonardo Pinheiro; Martins, Ricardo Silveira (Review of Business Management, 2015)
Objective – This paper aims to assess to what extent relational view assumptions can explain competitive advantages perceived in the industrial agglomeration contexts of small businesses. Design/methodology/approach – We used qualitative research; two furniture centers, Misassol (SP) and Ubá (MG), were examined through comparative data analysis. Data was collected through interviews with executives from 40 companies and 13 supporting organizations. The relational view and its assumptions point to factors that generate competitive advantage resulting from collaborative relationships between companies. Moreover, agglomerations provide intense relationships and are encouraged by governance entities. Findings – No competitive advantages clearly established due to relational gains were identified. The behavior of entrepreneurs in both centers tends strongly towards individualism. What agents identify as competitive advantages corresponds to situational or contextual factors in these centers and do not result from the realization of relational view assumptions, escaping from this paradigm. Relational gains can result only from subgroups that are formed through affinity, with no intervention from governance. Practical implications – Despite an agglomeration tendency within companies belonging to the furniture sector, a strong inclination towards individualism creates barriers to obtaining additional advantages resulting from relational gains, whether due to market regionalization, access of sales representatives, or logistics and tax costs, among other issues. However, actions in small groups are an important governance mechanism for that context. Contributions – Evaluate the assumptions of relational view and its explanatory power for competitive advantages in agglomerations of Brazilian furniture companies.